2013
DOI: 10.1186/1471-244x-13-260
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative care for patients with depression and diabetes mellitus: a systematic review and meta-analysis

Abstract: BackgroundDiabetic patients with depression are often inadequately treated within primary care. These comorbid conditions are associated with poor outcomes. The aim of this systematic review was to examine whether collaborative care can improve depression and diabetes outcomes in patients with both depression and diabetes.MethodsMedline, Embase, Cochrane library and PsyINFO were systematically searched to identify relevant publications. All randomized controlled trials of collaborative care for diabetic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 38 publications
3
104
0
1
Order By: Relevance
“…Given the expected increase in the number of women with DIP and depression, together with the particular challenges these women face in caring for themselves and their children, healthcare professionals need more specific guidance on management strategies for these patients. A collaborative care approach involving primary care physicians and specialists improves outcomes in non-pregnant patients with both diabetes and depression[78], and a similar model may be effective for the management of pregnant and postpartum women. Such guidance, however, should be based on sound research evidence, which, as our review demonstrates, is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Given the expected increase in the number of women with DIP and depression, together with the particular challenges these women face in caring for themselves and their children, healthcare professionals need more specific guidance on management strategies for these patients. A collaborative care approach involving primary care physicians and specialists improves outcomes in non-pregnant patients with both diabetes and depression[78], and a similar model may be effective for the management of pregnant and postpartum women. Such guidance, however, should be based on sound research evidence, which, as our review demonstrates, is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting a collaborative approach led to better depression outcomes and improved adherence to treatment for depression and diabetes, suggesting that there is a need to focus on collaborative care that emphasises improvement of the concurrent management of both conditions [20••].…”
Section: Collaborative Care – the Evidencementioning
confidence: 99%
“…[82][83][84][85][86][87] These models involve routine depression screening among individuals with uncontrolled diabetes, on-site care managers providing between-visit phone calls to assess diabetes self-care adherence, and on-site behavioral health providing brief interventions and SMG during the clinic visit. CCMs of diabetes and depression yield improvements in depression-related outcomes, [87][88][89][90][91] increased adherence to diabetes and depression self-management, 92,93 and decreased rates of mortality, compared to usual care. 94 Limited quantitative data are available supporting the association of collaborative care with improvement in HbA1c; however, one study showed that the incorporation of health coaching into diabetes management was associated with accelerated HbA1c reduction and improved mood as measured by Hospital Anxiety and Depression Scale (HADS).…”
Section: -73mentioning
confidence: 99%